The relationship between language and Pimrypie’s identities in donation discourse - Surin, Phongsatorn; Chotidilok, Suntaree; Satham, Sakaoduen (Humanities, Arts and Social Sciences Studies, 2025)
The donation discourse of Pimrypie, as represented on social media, not only persuades audiences to support charitable causes but also serves as a means through which Pimrypie constructs her identity, setting her apart from other donation discourse producers in online media. This has led to her becoming known as an outspoken yet charitable online seller. Significantly, her discourse has elevated her to a ‘socially desirable role model’ because her donation discourse emphasizes and foregrounds her positive identity traits. In another aspect, Pimrypie’s identity, as reflected in her donation discourse, may also yield potential business advantages. This research aims to analyze the relationship between language and Pimrypie’s identity as reflected in her donation discourse. The study employs qualitative research methods, collecting conversational texts from 82 videos on Pimrypie’s YouTube channel. The researchers use the concept of identity as a framework to analyze linguistic data. The findings reveal that Pimrypie’s identity in the donation discourse encompasses five aspects: 1) philanthropist identity, 2) empowering woman identity, 3) leadership identity, 4) independent woman identity, and 5) celebrity identity. The study shows that Pimrypie’s identity is constructed rationally and flexibly, allowing her to adapt to different contexts and remain in a favorable position. Ultimately, the researchers hope that this research will benefit readers by enhancing their understanding of identity construction and promoting media literacy regarding the media surrounding them.